2007
DOI: 10.1017/s1368980007000559
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of four dietary assessment methods in materially deprived households in England

Abstract: Objectives: Low-income households in the UK concentrate factors associated with poor record-keeping such as lower literacy, numeracy and English language skills. The present study aimed to (1) compare the validity and acceptability of three dietary survey methods against appropriate reference measures and (2) identify a method which was both valid and acceptable in low-income households. Design: Cross-sectional design comparing three 4-day dietary survey methods (multiple-pass 24-hour recall, food checklist an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
99
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(107 citation statements)
references
References 8 publications
1
99
0
3
Order By: Relevance
“…The use of three measures has proved more efficient for the triangulation of Na intake (29,30) . Another contribution of the present study was the inclusion of low-income individuals of marginal literacy, as such people tend to face greater difficulty in filling out questionnaires (11) .…”
Section: Discussionmentioning
confidence: 99%
“…The use of three measures has proved more efficient for the triangulation of Na intake (29,30) . Another contribution of the present study was the inclusion of low-income individuals of marginal literacy, as such people tend to face greater difficulty in filling out questionnaires (11) .…”
Section: Discussionmentioning
confidence: 99%
“…Three per cent of respondents did not know which method they preferred or felt there was no difference (9,10) . Respondents preferred the food checklist because it was easier than the other methods (49 %) and respondents did not have to do the recording themselves (as it was already written down for them; 26 %).…”
Section: Respondent Methods Preferencementioning
confidence: 99%
“…The weighed inventory, although it did not score highly and showed distinct disadvantages with problems relating to language, literacy and numeracy, was recommended as a reference method to provide information on the relative validity of the test methods and for comparisons with previous NDNS. These four methods were used in the subsequent method comparison study -the Low Income Diet Methods Study (LIDMS), the study design and initial findings of which have been reported elsewhere (9,10) . Briefly, LIDMS was carried out in 2001 and involved a crosssectional design, comparing three 4 d dietary survey methods (multiple-pass 24 h recall, food checklist and semi-weighed method) against reference measures in respondents living on a low income in London.…”
Section: Review Low Income Strengths Weaknesses Dietary Surveymentioning
confidence: 99%
See 1 more Smart Citation
“…Third, existing evidence relating dietary intake to vitamin D status is often limited due to imprecise dietary assessment methods, such as single 24-hr recall or Food Frequency Questionnaires (FFQ) [21][22][23][24][25]. Single 24-hr dietary recalls cannot account for intra-individual dietary variations that occur over time.…”
Section: Introductionmentioning
confidence: 99%